2020
DOI: 10.1155/2020/5105196
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Pathologic Bone Lesions Using Scout Computed Tomography (CT) Imaging

Abstract: The purpose of this study is to evaluate the benefit of reviewing scout CT images, obtained for routine oncologic surveillance, for the early identification of pathologic bony lesions. A retrospective review was conducted on patients who previously underwent surgical treatment by two orthopedic oncology surgeons at a tertiary care institution from 2009–2019 for pathologic lesions or fractures of the humerus or femur. Radiographic records were reviewed to identify patients in this cohort who had available scout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…In previous studies, CT was able to identify a primary site of malignancy in 88% of patients who presented with metastases of unknown origin. [8][9][10] Colello et al 11 demonstrated the importance of review of a Scout CT imaging review as a means to further identify potential metastatic lesions in the surrounding appendicular skeleton. 11 Additionally, a bone scan should be performed to assess the entire skeleton.…”
Section: Advanced Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, CT was able to identify a primary site of malignancy in 88% of patients who presented with metastases of unknown origin. [8][9][10] Colello et al 11 demonstrated the importance of review of a Scout CT imaging review as a means to further identify potential metastatic lesions in the surrounding appendicular skeleton. 11 Additionally, a bone scan should be performed to assess the entire skeleton.…”
Section: Advanced Imagingmentioning
confidence: 99%
“…[8][9][10] Colello et al 11 demonstrated the importance of review of a Scout CT imaging review as a means to further identify potential metastatic lesions in the surrounding appendicular skeleton. 11 Additionally, a bone scan should be performed to assess the entire skeleton. Bone scintigraphy makes use of technetium (Tc-99m) as the active agent and detects osteoblastic activity (Figure 3).…”
Section: Advanced Imagingmentioning
confidence: 99%
See 1 more Smart Citation